Retrospective Analysis and Family Feedback of Patients Who Underwent Tracheostomy in Pediatric Intensive Care Unit: Single Center, 10 Years of Experience - Ülkem KOÇOĞLU BARLAS; Hasan Serdar KIHTIR; Osman YEŞİLBAŞ; Mey Talip PETMEZCI; Nihal AKÇAY; Esra ŞEVKETOĞLU (Bezmiâlem Science, 2020)

(untitled)
Objective:The aim of this study was to investigate the patients who had undergone tracheostomy during hospitalization in our pediatric intensive care unit (PICU), to learn the satisfaction of the families, and to evaluate the effect of tracheostomy on the number of hospitalizations.Methods:The medical records of 80 patients who underwent tracheostomy in the PICU between 2006-2016 were retrospectively analyzed.Results:Fourty-one of our patients were male (51.25%) and 39 were female (48.75%). The mean age of males was 46.98 months (1-209 months) and girls was 43.44 months (1-205 months). Neurological system diseases (42.5%) were on the first place according to the current chronic diseases. Seventy-five patients (93.75%) were followed up with invasive mechanical ventilation and the mean duration of mechanical ventilation was 22.47±13.91 days. Only one patient (1.25%) had complication in early period. Forty one patients were contacted via telephone. Twenty-three families (56%) were satisfied with tracheostomy and 10 (24.5%) were not. The mean age of the dissatisfied group was statistically lower than the satisfied group (p=0.018). Of the 41 patients, 18 (44%) reported a decrease in the number of hospitalizations between before and after the tracheostomy and four (10%) reported an increase in the number of hospitalizations. The group with an increased number of hospitalizations had a significantly higher number of hospitalizations before the tracheostomy (p=0.028).Conclusion:The satisfaction levels of the families will be increased by increasing the tracheostomy care trainings given before discharge from the hospital, improving the home care services and ensuring the ease of transportation of these patients to the hospitals.